(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Information Technology (IT) has transformed the globe into a one village based oncommunications and other enterprises, thanks to technology. The Internet has revolutionized oureveryday lives and the manner in which we connect with others, as well as how we study and learn,work, and spend our time. Information Technology is important in many parts of life, bringing precision,speed, availability, and convenience to our daily lives. Individuals and businesses can use informationtechnology as a package of delivered programmes through physical infrastructure, and it plays a criticalpart in the expansion of Human Resources (HR). This article provides a brief overview of the importanceof information technology in human resource management. Today’s ruling leaders and top executivesrecognise the value of the Internet and digital systems in achieving organisational objectives.Information technology’s application and the Internet not only aids in achieving organisational goals, butalso in improving work evaluation.